Enhanced Healing Activity of Manuka Honey and Nitrofurazone Composite in Full-Thickness Burn Wounds in the Rabbit Model - Kulyar, Muhammad Fakhar-e-Alam; Ashfaq, Khurram; Aqib, Amjad Islam; Duan, Kun; Asif, Muhammad; Bhutta, Zeeshan Ahmad; Shoaib, Muhammad; Shabbir, Samina; Nawaz, Shah; Naseer, Muhammad Aamir; Sarwar, Iqra; Akhtar, Muhammad; et al. (Frontiers in Veterinary Science, 2022)
Burns cause many significant changes in metabolism and inflammatory reactions, leading to poor regeneration in animals and humans. A list of medicines to treat burns is available on the market. But due to the high cost of these medicines, these are unaffordable, especially for farmers of middle-class families of Africa and Asia. So, a low-cost complementary treatment has always been a topic of many researchers, and there is a dire need of time for the welfare of animals to save them. The current study was planned to scrutinize the therapeutic effects of manuka and nitrofurazone ointments on full-thickness burn wounds in rabbits. The healing efficacy was performed through wound contraction rate, hematological analysis, the thickness of dermis & epidermis, and collagen content percentage on days 0, 7, 14, 21, and 28th. Histopathology was performed after taking biopsy samples at the end of the research. Based on statistical analysis using wound healing time (days, D), the combination (MO+NT) resulted in a shorter period (27D±1) than the average healing time of controlled “PC” (36±2), Manuka ointment “MO” (31.33D±1.52) and nitrofurazone ointment “NT” (32±1). A significant decrease in RBC's count, MCV and MCH on days 7, 14, 21 and 28 in all treatments was noticed mainly in MO+NT. Furthermore, burns induced a significant difference (p < 0.05) in the WBCs count levels in the MO treated group. The level of PLT was not significantly different from the healthy control group. Histopathological assessment (epithelialization, fibrosis and angiogenesis) showed burn healing to be better in MO and MO+NT groups. In conclusion, the use of manuka with nitrofurazone led to a faster recovery than other treatments.